The Effectiveness of School Counselor as perceived by Educators and Students in Palestinian Secondary Schools - Shayeb, Marouf AbdelRaheem (Journal of Educational and Psychological Sciences, 2022)
This study aimed to determine the extent of the school counselors as perceived by counselors themselves, principals, teachers and students. In addition, the study sought to predict the counselor’s effectiveness in the light of several variables: gender, experience, academic qualification, and specialization stream of study, the study used descriptive survey procedures, research also used a questionnaire consisted of 118 items to collect the data of research. The sample of the study comprised of 104 counselors, 230 principals and 1,664 teachers and 2,376 students at Palestinian secondary schools in the West Bank. The sample represented 50% of all counselors and principals and 20% of students and teachers. The results of the study indicated that the degree of school counselor’s effectiveness, as perceived by counselors, principals, teachers and students, was high, results also reveled no statistically significant differences among averages of degrees of social counselor’s effectiveness domains which might be attributed to counselor’s experiences, academic qualifications and their interaction. Based on the current findings,134 the researcher recommends reinforce counseling services at Palestinian schools and also improve training and supervision services for school counselors.